JOINT WORK FILLED WITH POLEMICS: (Angelina Banović-Markovska, Zlatko Kramarić, Once Again Politics, Culture, Identity: Intercultural Dialogue 2, MI-AN, Skopje, 2024, pp. 396) (Journal of Contemporary Philology, 2025)
(Angelina Banović-Markovska, Zlatko Kramarić, Once Again  Politics, Culture, Identity: Intercultural Dialogue 2, MI-AN,  Skopje, 2024, pp. 396)
Keywords: review